Diseño del sistema integrado de gestión para el proceso de administración Colombia Mayor, conforme a las normas NTC ISO 9001:2015, NTC ISO 27001:2013 y el decreto 1072 de 2015 libro 2, parte 2, titulo 4°, capítulo 6 en el consorcio Colombia Mayor 2013. (2017)
The Integrated Management System design for the process Colombia Mayor Management, based on the standars NTC ISO 9001:2015, NTC ISO 27001:2013 and Decree 1072 of 2015 Book 2, Part 2, Title 4°, Chapter 6 for Consorcio Colombia Mayor 2013, is a document designed according to the institutional policies and the organizational strategies, that leads to a constant improvement of its processes, inner and outter customer satisfaction and minimize occupational risks. This document includes a current diagnose, based on the Consorcio overall facts: social, economic, political-cultural, the organizational structure, values and environment. This diagnose is the beggining for the Integrated Management System design based on the standars NTC ISO 9001:2015, NTC ISO 27001:2013 and Decree 1072 of 2015 Book 2, Part 2, Title 4°, Chapter 6 on the Comlombia Mayor Management process; allowing the organization to know the current situation inside the Consorcio and the requirements for the continual improvement. For the Integrated Management System design, based on the standars NTC ISO 9001:2015, NTC ISO 27001:2013 and Decree 1072 of 2015 Book 2, Part 2, Title 4°, Chapter 6 on the Comlombia Mayor Management process, was made the different parts of the organizational strategie (mission, vision, integral management policy and strategical objectives), the system description along with the processes improvement and it`s requirements to the interested parties, proposing an improved process diagram and safety management programs towards the accomplishment of the current regulations.